การประเมินผลการใช้ระบบสารสนเทศเพื่อการบริหารสมรรถนะข้าราชการครูและบุคลากรทางการศึกษาของสำนักงานเขตพื้นที่ การศึกษาประถมศึกษาเขตภาคเหนือตอนบน - ชื่นจิต วิชัยดิษฐ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objectives of study were to integrate an information technology evaluation system for the administrative and technical competency of teachers and government officials of the Primary Education Service in the upper Northern Region Office. The sample of this study consisted of participants 400 who use information technology regularly e.g. school administrator the education staff and teacher. The results of the study were as follows. Regarding the satisfaction of the information technology used, the respondents were satisfied the most e.g. the ability to manage. The system can reduce the period of time to get in information preparing the old way do not used the computer. The information was restricted to only the people who were involved, those who were not involved did not here access to the data. User were able to log-in and log-out with eases as well. Meanwhile the information technology content. The used satisfied in the obviousness and tight of the data. Regarding the knowledge and understanding in the information technology used; Find out the respondents have knowledge and understand about the electronic personnel record to a medium level. The knowledge and understanding of the most respondent was the record of the government teacher and the education, in to event that personnel information could added or modified from the menu. In relation to the problem and obstacle information technology system work was low level. The data searching was low to be able to. The previous view and the searching to slowly. The knowledge system and the application system were difficult cary out and the information was not updated effected that could not applied for workable.